Minimally open for surgical drainage of bilateral iliopsoas abscesses with Navigation-guided system: A case report - Ta-Chih Yu; Tai-Hsin Tsai; Yu-Feng Su; Yu-lin Chou; Huey-Jiun Ko; Cheng-Yu Tsai (Interdisciplinary Neurosurgery, 2020)
Iliopsoas abscess is a rare medical infection disease. Clinical finding was fluid or/with pus accumulated inside the iliopsoas muscle compartment. Most cases of iliopsoas abscess were unilateral site. Bilateral iliopsoas abscesses were rare and also difficult to treat clinically. Antibiotics alone or /with traditional percutaneous image-guided drainage such as Ultrasound-guided or Computerized Tomography-guided is a standard treatment. We describe a 41-year-old patient with bilateral iliopsoas abscess who presented to the Emergency Department with both lower legs pain. Computed tomography and Magnetic Resonance Imaging revealed the presence of bilateral low-density masses in bilateral iliopsoas muscle area indicative of bilateral iliopsoas abscesses. Antibiotics had been applied and Ultrasound-guided or Computerized Tomography-guided percutaneous drainage was recommended. Due to poor clinical assessment of traditional percutaneous image-guided drainage, we performed minimal open surgical drainage with Navigation-guided system. Iliopsoas abscess can be treated successfully with antibiotics alone or/with percutaneous image-guided drainage. Minimally open for surgical drainage with Navigation-guided system could be an effective and safe alternative optional method. To our knowledge, this is the first report of bilateral iliopsoas abscess with definitive drainage under minimally open for surgical drainage via Navigation-guided system.